Effect of grazing system on fetal development in Nellore cattle - Bergamaschi, MACM; Vicente, WRR; Barbosa, R. T.; Marques, J. A.; Freitas, A. R. (Elsevier B.V., 2004)
Intensive grazing systems for beef females, based on abundant availability of high quality forages and supplementary concentrates, may affect fetal development. The objective of this study was to determine the effect of grazing system on length of gestation, fetal development, and characteristics of the calf at birth. Twenty-four pregnant (bred to Nellore bulls) Nellore females were allocated into two groups. The control group (G1) grazed Brachiaria decumbens (signal grass) in a traditional (extensive) grazing system and the second group (G2) were managed on Panicum maximumcv. Tanzania 1 (Tanzania grass) in an intensive grazing system. Fetal development was evaluated by ultrasonography on days 31, 45, 59, 94, 122, 220, and 255 of gestation. The diameter of the amniotic and allantoic cavities, crown-rump length, circumference, and diameter of the head and ocular orbit were determined. At birth, calves were weighed and height, length, thoracic circumference, and ocular orbit and bi-parietal diameters were measured. There were no differences (P > 0.05) in fetal development. The G1 cows had a longer gestation period (4.5 days; P < 0.05) and their calves had greater (P < 0.05) weight, height, length, and thoracic circumference at birth. In conclusion, Nellore females raised under intensive pasture management conditions, had significantly shorter gestation and smaller calves at birth than those raised under extensive pasture management conditions. Therefore, adoption of new management practices (e.g. intensive pasture management), should take into consideration animal behavior and productivity. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: fetal growth; genotype; grazing system; Cattle; nellore; ultrasound